2020
DOI: 10.5867/medwave.2020.10.8066
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with COVID-19 admitted to a tertiary center in Chile: A cohort study

Abstract: Introduction Since the beginning of the COVID-19 pandemic, extensive research has been done on the prognosis of patients with SARS-CoV-2 associated with age, biodemographic conditions, comorbidities, social factors, clinical parameters, inflammatory blood markers, coagulation, biochemical and blood gas parameters, among others. Few studies have addressed this problem in Latin America, so it is of interest to know how the disease plays out in this region. Objective The purpose of our study is to evaluate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
1
2
0
1
Order By: Relevance
“…A similar pattern also manifested itself among the older patients, but less pronouncedly, possibly due to the prevalent accumulation of comorbidities among individuals in these strata. Our results confirmed the association of aging with the demand for healthcare resources and COVID-19-related deaths reported in different Brazilian states, (Sousa et al, 2020;Macedo et al, 2020;Cobre et al, 2020;Escosteguy et al, 2020;Moura et al, 2020;Leal et al, 2021;Policarpo et al, 2021;Bastos et al, 2020) in population restricted to a clinical condition or not, or even in national population studies, (Santos et al, 2021;de Souza et al, 2020;Nascimento et al, 2020;Marcolino et al, 2021;Castro et al, 2021) but also reported in studies in Latin America, Araujo et al, 2020;Elizondo et al, 2021;Galindo et al, 2021;Yacobitti et al, 2021;Ortiz-Prado et al, 2021) and in international cohorts (Pepe et al, 2021). Overall, frailty and the high prevalence of comorbidities made the elderly more susceptible to severe infection by COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…A similar pattern also manifested itself among the older patients, but less pronouncedly, possibly due to the prevalent accumulation of comorbidities among individuals in these strata. Our results confirmed the association of aging with the demand for healthcare resources and COVID-19-related deaths reported in different Brazilian states, (Sousa et al, 2020;Macedo et al, 2020;Cobre et al, 2020;Escosteguy et al, 2020;Moura et al, 2020;Leal et al, 2021;Policarpo et al, 2021;Bastos et al, 2020) in population restricted to a clinical condition or not, or even in national population studies, (Santos et al, 2021;de Souza et al, 2020;Nascimento et al, 2020;Marcolino et al, 2021;Castro et al, 2021) but also reported in studies in Latin America, Araujo et al, 2020;Elizondo et al, 2021;Galindo et al, 2021;Yacobitti et al, 2021;Ortiz-Prado et al, 2021) and in international cohorts (Pepe et al, 2021). Overall, frailty and the high prevalence of comorbidities made the elderly more susceptible to severe infection by COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…A few published papers have previously characterized the risk factors associated with COVID-19 mortality in Latin American patients (17,18) Therefore, the present study highlights multiple variables, including laboratory abnormalities and clinical features associated with COVID-19 mortality. The main findings in our study were significant associations between TBIL, ferritin, D-Dimer levels, dyspnea, GERD, and increased risk of mortality in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 81%
“…A few published studies have characterised the risk factors associated with COVID-19 mortality in Latin American patients 18 19 ; therefore, the present study highlights multiple variables, including laboratory abnormalities and clinical features associated with COVID-19 mortality. The main findings in our study were significant associations between respiratory distress, haemoglobin, LDH, PaO 2 /FiO 2 , CKD, ferritin, creatinine and leucocytes on admission, providing the landscape of multiple complex interactions associated with mortality in COVID-19.…”
Section: Discussionmentioning
confidence: 89%